The Role of Action Games in The Formation of Athletic Skills of Teenage Volleyball Players (Journal of Pedagogical Inventions and Practices, 2024)
This article analyzes the scientific basis for the formation of technical elements that can be performed by jumping using action games in the formation of jumping skills of teenage volleyball players in training sessions.